Parenting strategies and quality of family interaction in the children's perception - Ferreira, Carla Raquel Figueirêdo de Azevedo; Rivera, Giovani Amado; da Silva, Jandilson Avelino (Journal of Psychological Perspective, 2023)
The aim of this study is to perform a comprehensive analysis of children's and adolescents' perceptions of parenting strategies and the quality of family interaction, focusing on a comparison between fathers and mothers. A non-probabilistic sampling method based on convenience was employed to select 10 participants, consisting of male and female children and adolescents aged between 6 to 18 years old. The research instruments include a demographic questionnaire and the Family Interaction Quality Scale, which have been proven to be valid and reliable. Statistical analysis using a two-sample independent t-test reveals that the factors Involvement and Positive Communication have statistical significance with a p-value less than 0.05. Scores for these two factors were higher for mothers compared to fathers. These results highlight the importance of considering the roles and approaches taken by both parents in the context of family interaction quality. The findings are expected to serve as a reference in designing more effective family education interventions or programs, especially in improving the dynamics and quality of interactions among family members from the children and adolescents' perspective.